Solitary confinement placement and post-release mortality risk among formerly incarcerated individuals: a population-based study - Christopher Wildeman, ProfPhD; Lars H Andersen, PhD (Elsevier, 2020)
Summary: Background: With more than 10 million people incarcerated worldwide, some of whom will have experienced solitary confinement, a better understanding of health and mortality after release is needed. The aim of this study was to assess the relationship between placement in solitary confinement and mortality in the 5 years following release among formerly incarcerated individuals. Methods: In this population-based study we used data from Danish administrative registers and administrative dataset from the Danish Prison and Probation Service. We linked information on all Danish individuals who had been incarcerated for more than 7 days during 2006-11, with information on mortality for the 60 months following release. We used Cox proportional hazards models to estimate the association between being placed in solitary confinement and mortality (death and cause of death) among formerly incarcerated Danish individuals, controlling for several possible confounders (prison security level, release year, sentence length, reason for conviction, age at admission, sex, ethnic minority background, and education level) and using a reference group of incarcerated Danish individuals who had been sanctioned for in-prison infractions but not placed in solitary confinement in some models. Findings: Our study included 13 776 individuals, which translated to 812 374 person-months of exposure to the risk of mortality up to Dec 31, 2016. Formerly incarcerated Danish individuals who spent time in solitary confinement had higher overall mortality 5 years after release (4·5%) than did those who had not spent time in solitary confinement (2·8%; p<0·0001). After adjusting for possible confounders, our results suggested an association between solitary confinement and elevated mortality due to non-natural causes (hazard ratio 2·342, 95% CI 1·527-3·592). We did not identify a significant association with natural causes. Interpretation: The results from these analyses indicate that solitary confinement placement might be a key moderator of the association between a history of incarceration and post-release outcomes. Our findings suggest that incarcerated individuals ever placed in solitary confinement are a vulnerable population in need of interventions. Funding: ROCKWOOL Foundation.